2014
DOI: 10.1116/1.4903366
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on zinc oxysulfide-Zn(O,S) films synthesized by atomic layer deposition for Cu(In,Ga)Se2 solar cells

Abstract: Thin films of Zn(O,S) were deposited by atomic layer deposition from diethylzinc, water (H2O), and hydrogen sulfide (H2S). First, a study on the influence of the H2S/(H2O+H2S) pulse ratio from pure ZnO to pure ZnS was performed at deposition temperature Tdep=120 and 200 °C. Zn(O,S) films had higher S content than expected, and this effect was stronger at Tdep=200 °C. Then, Zn(O,S) films have been synthesized over the range of temperature 120–220 °C at the constant H2S/(H2O+H2S) pulse ratio of 9%. For Tdep&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Allowing atomic scale control of film thickness and composition, atomic layer deposition (ALD) enables the necessary finetuning of the Zn(O,S) system. 10,[14][15][16][17] ALD was used to deposit Zn(O,S) by alternating sequences of diethylzinc (DEZ), H 2 O and H 2 S exposures, where Zn(O,S) formation was suggested to proceed via the incorporation of sulfur into the ZnO matrix, causing changes to the local bonding environment. 7,18,19 Samples named ZnO and ZnS served as our references.…”
Section: Introductionmentioning
confidence: 99%
“…Allowing atomic scale control of film thickness and composition, atomic layer deposition (ALD) enables the necessary finetuning of the Zn(O,S) system. 10,[14][15][16][17] ALD was used to deposit Zn(O,S) by alternating sequences of diethylzinc (DEZ), H 2 O and H 2 S exposures, where Zn(O,S) formation was suggested to proceed via the incorporation of sulfur into the ZnO matrix, causing changes to the local bonding environment. 7,18,19 Samples named ZnO and ZnS served as our references.…”
Section: Introductionmentioning
confidence: 99%
“…For ZnO x S y , this reaction has been reported to have a negative Gibbs energy of −75.5 kJ/mol and is thus thermodynamically favorable. 14 Similarly, Choi et al showed through a density functional theory (DFT) study that for SnO x S y , the exchange of a surface OH group with H 2 S is exothermic (−46.0 kJ/mol). 6 The supercycle-based approach to prepare ALD TiO x S y films used in this work combines ALD TiO x with an ALD TiS x recipe that was recently developed in our group for the synthesis of 2D TiS x -based films.…”
Section: ■ Introductionmentioning
confidence: 92%
“…For ZnO x S y , this reaction has been reported to have a negative Gibbs energy of −75.5 kJ/mol and is thus thermodynamically favorable . Similarly, Choi et al showed through a density functional theory (DFT) study that for SnO x S y , the exchange of a surface OH group with H 2 S is exothermic (−46.0 kJ/mol) …”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations